(untitled) (Research, Society and Development, 2024)
Tuberculosis is an infectious and transmissible disease that despite being an old disease, tuberculosis remains a public health problem. As it’s an opportunistic infection, several factors can worsen the therapeutic outcome of the disease in question. This study is a quantitative research among patients diagnosed with tuberculosis and its related conditions in the population of the State of Paraná between the years 2015 and 2023. As a research instrument, the Information and Notifiable Diseases System database was used (SINAN), through the Information Technology Department of the Unified Health System (DATASUS), to measure the epidemiological prolife and diseases, as well as the outcome of patients diagnosed with tuberculosis. At the end of the study, it was found that the age group between 20 and 59 years old are prevalent in relation to cases of tuberculosis, as well as White men, with patients with AIDS and Mental Illnes being more susceptible to illnesses.